Ozone: A Pollutant and a Protector Gas - Subedi, Thaneshwar (Janapriya Journal of Interdisciplinary Studies, 2017)
The natural balance of ozone in the stratosphere is due to continuous formation of ozone from oxygen and dissociation of it into oxygen in presence UV radiation. Amount of ozone can be determined by colorimetric method. It is poisonous gas near the earth surface in biosphere and protective shield in stratosphere. Depletion of ozone layer and formation of hole in it is due to reaction of CFCS, NOx, OH, H2O with ozone in stratosphere. Direct entrance of UV -B in the biosphere causes skin cancer, cataract, blindness, suppression of immune system degradation of plastics, reduction of food, vegetable & fish production and then alters the overall ecosystem. Protector ozone layer can be saved by replacing CFCS by HCFCS, by reducing supersonic flight & nuclear explosions, by refilling ozone in depleted area and by conducting public awareness about importance of ozone layer. Janapriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), page: 124-132